Axon regeneration: an issue of translation - Schaeffer, Julia; Belin, Stephane (Comptes Rendus Biologies)
In the mammalian central nervous system (CNS), adult neurons fail to regenerate spontaneously upon axon injury, which leads to a permanent and irreversible loss of neuronal functions. For more than 15 years, much effort was invested to unlock axon regrowth programs based on extensive transcriptomic characterization. However, it is now well described that mRNA and protein levels correlate only partially in cells, and that the transcription process (from DNA to mRNA) may not directly reflect protein expression. Conversely, the translation process (from mRNA to protein) provides an additional layer of gene regulation. This aspect has been overlooked in CNS regeneration. In this review, we discuss the limitations of transcriptomic approaches to promote CNS regeneration and we provide the rationale to investigate translational regulation in this context, and notably the regulatory role of the translational complex. Finally, we summarize our and others’ recent findings showing how variations in the translational complex composition regulate selective (mRNA-specific) translation, thereby controlling CNS axon regrowth.